2013
DOI: 10.2147/ijn.s30725
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes and nanotechnology in drug development: focus on ocular targets

Abstract: Abstract:Poor drug delivery to lesions in patients' eyes is a major obstacle to the treatment of ocular diseases. The accessibility of these areas to drugs is highly restricted by the presence of barriers, including the corneal barrier, aqueous barrier, and the inner and outer blood-retinal barriers. In particular, the posterior segment is difficult to reach for drugs because of its structural peculiarities. This review discusses various barriers to drug delivery and provides comprehensive information for desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
95
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 62 publications
(60 reference statements)
0
95
0
1
Order By: Relevance
“…28 Drug payloads can be either entrapped within the dendrimer scaffold via the generation of noncovalent complexes or linked to the dendrimer surface via covalent conjugation, so dendrimers can incorporate a lower amount of drugs than other carriers. 29 Covalently constructed dendritic macromolecules have the advantage of more specific control over drug release and may be designed to limit drug release in the systemic circulation and to trigger release under tumorspecific conditions (Table 2). 30 Dendritic polymers have recently been shown to improve the delivery of doxorubicin and other cytotoxic drugs to solid tumors and to reduce their accumulation in noncancerous tissues.…”
Section: Dendrimersmentioning
confidence: 99%
“…28 Drug payloads can be either entrapped within the dendrimer scaffold via the generation of noncovalent complexes or linked to the dendrimer surface via covalent conjugation, so dendrimers can incorporate a lower amount of drugs than other carriers. 29 Covalently constructed dendritic macromolecules have the advantage of more specific control over drug release and may be designed to limit drug release in the systemic circulation and to trigger release under tumorspecific conditions (Table 2). 30 Dendritic polymers have recently been shown to improve the delivery of doxorubicin and other cytotoxic drugs to solid tumors and to reduce their accumulation in noncancerous tissues.…”
Section: Dendrimersmentioning
confidence: 99%
“…Methods such as hydrogels, polymeric micelles, and nanocarriers were widely used in this area (Li et al, 2008;Shen et al, 2009;Gupta et al, 2010;Li et al, 2012;Liu et al, 2012;Gan et al, 2013). Liposomes, a kind of closed vesicles composed of a phospholipid bilayer and an aqueous phase (Honda et al, 2013), have been serving as a promising ocular drug delivery method for the past decade (Li et al, 2009). Studies have demonstrated that by applying this method, a controlled drug release as well as membrane permeability can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Multifunctional nanoemulsions for oral and intravenous delivery: Gadolinium-loaded nanoemulsion has been utilized for brain imaging in animal studies [114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133]134]. This imaging technology could be utilized for imaging within the eye to observe the results of various drug delivery modalities.…”
Section: Applications Of Nanoparticulate Transscleral Drug Delivery Smentioning
confidence: 99%